Pemetaan Sebaran Objek Wisata di Kawasan Pantai Indah Kapuk (PIK) Menggunakan Sistem Informasi Geografis - Ashila Fitria Zahra; Leysha Adinda Citra; Gita Sukma Irvi Lestari; Rizqa Rahmawati; Raihan Ali Ertono; Ahman Sya (Geosfera: Jurnal Penelitian Geografi, 2025)
Pantai Indah Kapuk (PIK) area has transformed into an integrated urban tourism destination, yet its development lacks comprehensive spatial analysis regarding the distribution pattern of its tourist attractions. This study aims to map and analyze the distribution of tourism objects in the PIK area using a Geographic Information Systems (GIS) approach. The method used is spatial descriptive with coordinate data from satellite imagery, which is then analyzed to identify distribution patterns and clustering. The results show that tourism objects are concentrated unevenly, forming function-based clusters along the reclaimed coastal corridor, dominated by culinary, recreation, and shopping tourism. Key findings reveal spatial utilization disparities, a clear waterfront-oriented development pattern, and governance complexity due to the area being divided into three different administrative regions. The study concludes that this GIS mapping provides a critical spatial database for spatial planning and more integrated, sustainable tourism development that can address policy fragmentation across regional boundaries.